La expansión del portugués en Oriente en el siglo XVI y la documentación jesuítica - Ángel, MARCOS DE DIOS; Eduardo Javier, ALONSO ROMO (Revista de Filología Románica, 2002)
This essay is the result of the study of c. 2000 pages, a small part of the writings of the Jesuits who worked in the portuguese domains in the far East, starting from 1542. Our text reveals the great importance of the Society of Jesus’s missions in the expansion of the portuguese language in those lands. Furthermore, the investigation of this documentation allows us to analyze specific features of the portuguese language in the mid 16th century. Some archaisms were preserved and certain innovations took place, not allways reflected by the writers of those days. From the point of view of the lexicon, this essay highlights the abundance of words that have cult or oriental origin. In appendix we offer a list of almost two hundred words that we consider, with the necessary caution, to be registrered for the first time in Portuguese.